1997
DOI: 10.1017/s0022112097006368
|View full text |Cite
|
Sign up to set email alerts
|

Centreline velocity decay measurements in low-velocity axisymmetric jets

Abstract: The streamwise velocity profiles of low-velocity isothermal axisymmetric jets from nozzles of different diameters were measured and compared with previous experimental data. The objective of the measurements was to examine the dependence of the diffusion of the jet on the outlet conditions. As the outlet velocity was decreased, the centreline velocity decay coefficient began to decrease at an outlet velocity of about 6 m s −" .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
31
1
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 9 publications
14
31
1
3
Order By: Relevance
“…Indeed, this entrainment coefficient definition reflects that the air entrainment rate is responsible for the increase of the total jet flow rate with downstream distance. This is further confirmed by the experiments by Crow et al [5] or Malmström et al [35] in the twophase jet flow near field region, i.e., at a downstream distance of less than ten nozzle outlet diameters, elucidating that the entrainment coefficient in this region is lower than that in the Similarity region of the jet, i.e., at a downstream distance of greater than thirty nozzle outlet diameters.…”
Section: Literature Surveysupporting
confidence: 70%
“…Indeed, this entrainment coefficient definition reflects that the air entrainment rate is responsible for the increase of the total jet flow rate with downstream distance. This is further confirmed by the experiments by Crow et al [5] or Malmström et al [35] in the twophase jet flow near field region, i.e., at a downstream distance of less than ten nozzle outlet diameters, elucidating that the entrainment coefficient in this region is lower than that in the Similarity region of the jet, i.e., at a downstream distance of greater than thirty nozzle outlet diameters.…”
Section: Literature Surveysupporting
confidence: 70%
“…The reported values on K commonly span between 4.0 -6.7 (see for example the review articles by Lipari and Stansby (2011) and Abdel-Rahman (2010)), although Malmström et al (1997) reported values below 4 for jets with very low inlet velocity. For the virtual origin ( ) reported values in the literature show significant spread.…”
Section: Research Questionmentioning
confidence: 99%
“…The spreading rate of a single round jet is in the order of 0.1 (see for example Malmström et al (1997)). …”
Section: Research Questionmentioning
confidence: 99%
“…Son Siebers y Higgins a lo largo de una serie de trabajos experimentales [69][70][71] los que estudian el fenómeno con detalle para un chorro Diesel inyectado en una cámara de volumen constante. Estos autores miden la longitud de lift-off a partir de la quimioluminiscencia del OH [72], y no a partir de la incandescencia del hollín como habían hecho Winklhofer o Larsson. En realidad, la longitud de lift-off indica la distancia a la cual está ubicada la zona de reacción premezclada que presenta el modelo conceptual de combustión en la fase cuasi-estacionaria, y a dicha distancia no hay hollín presente, sino que este aparece aguas abajo de esa zona (figura 2.8 30 ) y del aire en cámara (densidad, temperatura y concentración de oxígeno) que cubren, de manera más completa que Bergstrand et al, el rango esperable de condiciones en un motor Diesel de inyección directa.…”
Section: Lift-offunclassified
“…Se observa que, en una posición axial dada, la velocidad y la fracción de mezcla toman valores más elevados en el caso de combustión que en el de mezcla. Dicho de otra forma, la coordenada axial para la cual se alcanza un determinado grado de mezcla es mayor en el caso de un chorro en combustión que en el de mezcla 72 . En consecuencia, existen cambios en el tamaño del chorro y en el proceso de mezcla que las leyes de escalado desarrolladas hasta ahora no pueden tener en cuenta, y que dependen fundamentalmente del proceso de combustión.…”
Section: La Fracción De Mezcla Y Las Relaciones De Estadounclassified